A system of UAV application in indoor environment. Issue 1 (1st January 2016) - Khosiawan, Yohanes; Nielsen, Izabela
Abstract : In recent years, there has been an increased demand in the use of multiple unmanned aerial vehicles (UAVs) in indoor environments such as material handling task in a manufacturing environment and plant/environment monitoring task in a greenhouse. However, there is a lack of work reported on this topic. This paper presents a detailed study on several UAV systems and UAV scheduling systems. It is followed by a proposed system of UAV application in indoor environment, which comprises components of UAV system addressed in detail; focused on scheduler as the heart of operations. Consequently, system architecture of UAV scheduling system is presented and the framework of scheduler component is included. Scheduler component works in a phased manner to provide a systematic abstraction and achieve an efficient computation time. This study serves as a reference guide for UAV application in indoor environment.